Efficacy and serious adverse events profile of the adjuvanted recombinant zoster vaccine in adults with pre-existing potential immune-mediated diseases: a pooled post hoc analysis on two parallel randomized trials. (10th September 2020) - Dagnew, Alemnew F; Rausch, Debora; Hervé, Caroline; Zahaf, Toufik; Levin, Myron J; Schuind, Anne; ,
Abstract: Abstract Objective: In the ZOE-50 (NCT01165177) and ZOE-70 (NCT01165229) phase 3 clinical trials, the adjuvanted recombinant zoster vaccine (RZV) demonstrated ≥90% efficacy in preventing herpes zoster (HZ) in all age groups ≥50 years. Given the increased HZ risk associated with certain underlying autoimmune diseases or their treatment regimes, we conducted a post hoc analysis of RZV's efficacy against HZ and safety profile [specifically, the occurrence of serious adverse events (SAEs)] in ZOE-50/70 participants who reported pre-existing potential immune-mediated diseases (pIMDs) at enrolment and were not on immunosuppressive therapies. Methods: Adults aged ≥50 (ZOE-50) and ≥70 (ZOE-70) years were randomized to receive two doses of RZV or placebo 2 months apart. In this subgroup analysis of participants with at least one pIMD at enrolment, the efficacy was calculated for two-dose recipients who did not develop confirmed HZ before 30 days post-dose 2. SAE occurrence was evaluated for all participants who received at least one dose. Results: Of the 14 645 RZV and 14 660 placebo recipients from the ZOE-50/70 studies, 983 and 960, respectively, reported at least one pre-existing pIMD at enrolment and were included in these analyses. The most frequent pre-existing conditions were psoriasis, spondyloarthropathy and RA. Efficacy against HZ was 90.5% (95% CI: 73.5, 97.5%) overall with the lowest being 84.4% (95% CI: 30.8, 98.3%) in the 70–79-year-old age group. SAEs and fatal SAEs were similar between RZV and placebo recipients. Conclusion: In ZOE-50/70 participants with pre-existing pIMDs, RZV was highly efficacious against HZ and SAE incidence was similar between RZV and placebo recipients. Trial registration: ClinicalTrials.gov, https://clinicaltrials.gov, NCT01165177 (ZOE-50), NCT01165229 (ZOE-70). Graphical Abstract: